Andarele Dance: The Female Body Empowerment Through The Sensual Movement - Cristina Duque Martinez (Graduate School of Institut Seni Indonesia Yogyakarta, 2023)
This article commences with the historical-epistemological background of the sensual Andarele dance from Esmeraldas, Ecuador, aiming to comprehend the symbolic and social conception of the body. Employing a qualitative methodology, it scrutinizes the relationship between the Andarele dance and social and gender theories. The article's primary objective is to engender a discussion concerning female empowerment, with due consideration given to analyzing data on women's experiences in Ecuador and theoretical studies elucidating the benefits of women's body movement as a novel instrument for self-awareness. This process enables women to recognize their creative potential, empower themselves, and embark on emancipation. Consequently, their bodies become a transversal axis that connects and communicates with the external world.Â Tari Andarele: Pemberdayaan Tubuh Wanita melalui Gerakan Sensual Abstrak Artikel ini diawali dengan latar belakang sejarah-epistemologis tarian sensual Andarele dari Esmeraldas, Ekuador, yang bertujuan untuk memahami konsepsi simbolis dan sosial tentang tubuh. Menggunakan metodologi kualitatif, penelitian ini meneliti hubungan antara tarian Andarele dengan teori sosial dan gender. Tujuan utama artikel ini adalah untuk melahirkan diskusi tentang pemberdayaan perempuan, dengan pertimbangan diberikan untuk menganalisis data pengalaman perempuan di Ekuador dan studi teoretis menjelaskan manfaat gerakan tubuh perempuan sebagai instrumen baru untuk kesadaran diri. Proses ini memungkinkan perempuan untuk mengenali potensi kreatif mereka, memberdayakan diri mereka sendiri, dan memulai emansipasi. Akibatnya, tubuh mereka menjadi sumbu transversal yang menghubungkan dan berkomunikasi dengan dunia luar.